2013
DOI: 10.1093/cid/cit520
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception Risk and Disease Prevention Associated With Rotavirus Vaccines in Australia's National Immunization Program

Abstract: We found a similarly increased risk of IS after both vaccines, but the balance of benefits and risks at population level was highly favorable, a finding likely to extend to other settings despite varying incidence of IS and potentially higher morbidity and mortality from both gastroenteritis and IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 29 publications
9
131
2
4
Order By: Relevance
“…Title and abstract screening resulted in the identification of 16 potentially relevant publications. Ten of these 16 studies met the inclusion criteria for the meta-analysis (Table 1) (18,(26)(27)(28)(29)(30)(31)(32)(33)(34). The publications not included in the full text screening are listed as references e2-e7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Title and abstract screening resulted in the identification of 16 potentially relevant publications. Ten of these 16 studies met the inclusion criteria for the meta-analysis (Table 1) (18,(26)(27)(28)(29)(30)(31)(32)(33)(34). The publications not included in the full text screening are listed as references e2-e7.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies included in the review, 7 provided data on the risk of intussusception after RV1 vaccination (18, 26, 29, 30, 32-34) and 4 on the risk after RV5 (27,29,31,34). One study reported only the results for both vaccines together (28).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This risk was shown to be proportional to the time from birth to first dose with delayed dosing resulting in an increased risk of life-threatening intussusception [7]. Although pre-licensure studies showed no significant increase in intussusception for both current vaccines compared with placebo, data now suggest there is an increased risk, albeit substantially lower than with RotaShield [8,9]. The risk of intussusception following current RV vaccines administered within the correct time window is 1.5-6 per 100,000 compared with a 10-fold higher risk of 1 per 10,000 with RotaShield.…”
Section: Rv Vaccines -The Importance Of Timely Immunizationmentioning
confidence: 99%
“…15 This is likely attributable to the reluctance of some pediatricians and public health physicians to recommend rotavirus vaccination due to a slight increase of intussusception among children vaccinated with RV1 and RV5, which was observed in other countries, especially after the first dose. 16 …”
Section: Introductionmentioning
confidence: 99%